2016
DOI: 10.2106/jbjs.15.00445
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Hip Arthroscopy According to Sex and Age

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(170 citation statements)
references
References 54 publications
4
161
3
2
Order By: Relevance
“…This information will help guide surgeons and patients in choosing the optimal treatment algorithm. [15][16][17][18][19][20] Preoperative predictors of clinically significant sport function level at 2 years after hip arthroscopy are unclear. Westermann and colleagues 21 identified that mental health, activity level, sex, and smoking predict greater baseline pain and decreased baseline function before hip arthroscopy; however, the authors did not evaluate the efficacy of the intervention or predictors of postoperative pain and function.…”
Section: Introductionmentioning
confidence: 99%
“…This information will help guide surgeons and patients in choosing the optimal treatment algorithm. [15][16][17][18][19][20] Preoperative predictors of clinically significant sport function level at 2 years after hip arthroscopy are unclear. Westermann and colleagues 21 identified that mental health, activity level, sex, and smoking predict greater baseline pain and decreased baseline function before hip arthroscopy; however, the authors did not evaluate the efficacy of the intervention or predictors of postoperative pain and function.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Markedly improved functional outcome scores after hip arthroscopy have been reported, with no difference between sexes in patients aged ,45 years. 51,52 Further investigation of sex-based differences in the clinical presentation, relevant anatomy, and surgical management of FAI is necessary to elucidate factors markedly associated with patient outcomes. For example, recognizing that females have higher rates of pelvic anteversion coupled with greater ligamentous laxity might suggest that surgical osteoplasty would be beneficial in this population, even in the setting of radiographically smaller impingement lesions.…”
Section: Figurementioning
confidence: 99%
“…14 In a study of 150 hip arthroscopy patients at 2-year follow-up, Frank and colleagues found that age greater than 45 years and female sex were associated with inferior patient-reported outcomes. 31 Similarly, in other arthroscopic orthopaedic procedures age has also been identified as a predictor of adverse outcomes, with one study assessing knee arthroscopy finding that older age (40-65 years vs < 40 years old) was an independent predictor of aggregated total short-term complications, with 1.5 times increased risk. 32 In shoulder arthroscopy, age greater than 60 years was also identified as an independent risk factor for short-term complications after arthroscopic rotator cuff repair.…”
Section: Discussionmentioning
confidence: 99%